Uso da manufatura aditiva na otimização do processo de fabricação de moldes de alumínio fundido em uma empresa do ramo calçadista - Heinen, Douglas Ricardo (Universidade do Vale do Rio dos Sinos, 2021)
New technologies are making the world and business to be revolutionized. Industry 4.0 known as the fourth industrial revolution is based on the transformation that takes place in the digital revolution, characterized by the convergence of innovative technologies, such as additive manufacturing. In this context, this research explores the impacts of the use of Additive Manufacturing in the manufacture of models used for casting aluminum molds in the footwear industry. To meet this objective, a systematic review of the literature on the subject was initially carried out. From this review, propositions guide the elaboration of a questionnaire for interviews carried out with managers of the company where the case study was carried out. To carry out the case study, the mold manufacturing process was mapped using conventional manufacturing, and using additive manufacturing. Afterwards, the content analysis was performed, which sought to identify convergences and divergences between literature and practice. As a result, we highlight the reduction in lead time, the reduction in product development time, in addition to the increase in the availability of resources in the company under study. However cycle time and low resolution and quality are still points of improvement for the technology. Given the above, additive manufacturing is consolidated as a great technological advance in manufacturing, improving processes and helping in the strategic positioning of the industry..
Keywords: Additive manufacturing; Industry 4.0; Conventional manufacturing; Manufatura aditiva; Indústria 4.0; Manufatura convencional